The “Illusion” of Social Research/ Action. Reflections on Neo-Colonial Pedagogy - Jabłoński, Maciej (Qualitative Sociology Review, 2021)
In the text, the author demonstrated that regardless of the prevailing regime, the State, by relying on separate laws for people with disabilities (or any other minority group), has created and continues to create colonies of sorts. In the first part of the article, the author presented the difference between postcolonialism and neo-colonialism in relation to people with disabilities and in Disability Studies. Afterward, he highlighted the illusory nature of research and, above all, educational activities in favor of people with disabilities. He argues that in the case of this group of people, we are dealing with neo-colonial pedagogy rather than a postcolonial one.